Practical Strategies and Guidance for Contextual Literature Reviews in Urban Studies - Hisham Abusaada; Abeer Elshater (Societies, 2025)
This conceptual article introduces an alternative perspective on the notion of the urban context for early-career researchers interested in developing academic writing through literary narratives. It brings together two distinct conceptualizations of context. The first is a philosophical approach rooted in interpretive traditions within the humanities and social sciences. The second is a spatial–societal approach commonly adopted in architecture, urban planning, and urban design. By bridging these perspectives, our article aims to enrich interdisciplinary discourse and support more nuanced understandings of urban environments in narrative-based research. The question posed by this conceptual article is given as follows: How can adopt a historical–philosophical contextual approach to literary narratives support the development of non-traditional narrative forms and offer a strategic foundation for early-career researchers? This study adopts a qualitative research approach to examine the role of context in knowledge production. A linear snowball sampling was employed to identify relevant sources, followed by qualitative content analysis to extract key insights. The outcomes integrate perspectives from historians, interpretive philosophers, and urban specialists. The findings provide practical strategies to support early-career researchers in developing historically informed, contextually grounded literary narratives, particularly within non-traditional academic formats.